2009
DOI: 10.1097/acm.0b013e3181bb1f0d
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalistsʼ Involvement in Pediatrics Training: Perspectives From Pediatric Residency Program and Clerkship Directors

Abstract: The role of hospitalists in resident and student education will likely continue to evolve over the next decade.Additional refinement of the roles and responsibilities of hospitalists will address lingering concerns in some programs about resident autonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…The growth of PHM has prompted an in-depth look at the field by the ABP. 1,12,13 PHM programs appear to have become part of the fabric of pediatric care, with the majority of hospitals with PHM programs planning to continue the programs despite the need to pay for value-added by hospitalists beyond revenue received for their direct clinical service. 13 Looking forward, when the Institute of Medicine recommendations to further restrict resident work hours to 16 hour shifts are implemented, many programs plan on increasing their PHM programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth of PHM has prompted an in-depth look at the field by the ABP. 1,12,13 PHM programs appear to have become part of the fabric of pediatric care, with the majority of hospitals with PHM programs planning to continue the programs despite the need to pay for value-added by hospitalists beyond revenue received for their direct clinical service. 13 Looking forward, when the Institute of Medicine recommendations to further restrict resident work hours to 16 hour shifts are implemented, many programs plan on increasing their PHM programs.…”
Section: Discussionmentioning
confidence: 99%
“…12 Training programs should consider this impact when selecting attending hospitalists and supporting their roles as mentors and educators. As residents finish their training and seek positions as pediatric hospitalists, programs need to be aware that a significant percentage of residents in our survey see PHM as a short-term career option and/or fail to see a difference between a PH job and their own.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, most studies have shown that pediatric hospitalists are generally rated as better teachers than their traditional attending counterparts and that residents did not feel that hospitalists impacted negatively on their autonomy [40 ,41]. Freed et al [42 ] explored these issues further through a survey of 170 residency directors and 131 clerkship directors. This survey supports the theory that pediatric hospitalists are heavily involved in clinical teaching, especially when it comes to issues around, for example, quality, efficiency, and resource utilization.…”
Section: Hospitalists As Teachersmentioning
confidence: 98%
“…13 A generalist philosophy is central to what many hospitalists teach and role model. The generalist's philosophy includes concepts such as a broad outlook, integration, continuity, and collaboration.…”
Section: Teaching and Role Modelingmentioning
confidence: 99%